2018
DOI: 10.5395/rde.2018.43.e40
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile bond strength of CAD/CAM-fabricated polymer-ceramics to different adhesive resin cements

Abstract: ObjectivesThis study evaluated the microtensile bond strength (µTBS) of polymer-ceramic and indirect composite resin with 3 classes of resin cements.Materials and MethodsTwo computer-aided design/computer-aided manufacturing (CAD/CAM)-fabricated polymer-ceramics (Enamic [ENA; Vita] and Lava Ultimate [LAV; 3M ESPE]) and a laboratory indirect composite resin (Gradia [GRA; GC Corp.]) were equally divided into 6 groups (n = 18) with 3 classes of resin cements: Variolink N (VAR; Vivadent), RelyX U200 (RXU; 3M ESPE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Despite the remarkable optical properties and natural tooth-like appearance of the ceramics, their potential disadvantages include abrasion of the opposing dentition because of their high hardness and risk of brittle fracture and chipping [ 9 , 10 ]. In contrast, resin composites cause less wear to the opposing dentition, are less brittle, are easier to repair and are more fracture resistant [ 11 13 ]. Nonetheless, their color stability is inferior, and the material wears down more quickly than ceramics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the remarkable optical properties and natural tooth-like appearance of the ceramics, their potential disadvantages include abrasion of the opposing dentition because of their high hardness and risk of brittle fracture and chipping [ 9 , 10 ]. In contrast, resin composites cause less wear to the opposing dentition, are less brittle, are easier to repair and are more fracture resistant [ 11 13 ]. Nonetheless, their color stability is inferior, and the material wears down more quickly than ceramics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result agreement with Cinar et al (2019) 18 they found the highest SBS for Lava ultimate (18.73±1.91 MPa) was obtained in group sandblast + silane with self-adhesive resin cement. Also the Sadighpour et al (2018) 19 they showed self-adhesive resin cement (RelyX U200) higher than multistep adhesive resin cement (Panavia).…”
Section: Discussionmentioning
confidence: 96%
“…In the present laboratory study, three types of ceramic [21][22][23] and three types of resin cements 24) were used. These materials are commonly used for prosthetic rehabilitation of anterior teeth.…”
Section: Discussionmentioning
confidence: 99%